(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Objective: The study was designed to investigate the in vivo effects of black and green tea consumption on serum lipid profile and cardiac function in hyperlipidemic rats. Methods: 24 male Wistar rats, average weight 125 g were sorted into four groups: A, B, C and D. Normal control group (A) were fed standard rat chow; the remaining three groups (B, C and D) received rat chow supplemented with 2% (w/w) cholesterol to induce hypercholesterolemia. Group C and D were administered 40 mg/ml of black and green tea respectively while group B (hyperlipidemic control) were not treated. The feeding and tea administration lasted 6 weeks. Results: Significant reduction in body weight and heart weight index was recorded in rats administered black and green tea compared with the untreated group. Black and green tea consumption also caused significant decrease in total cholesterol, LDL-cholesterol, triglycerides and coronary heart disease (CHD) risk ratio accompanied with elevated HDL-cholesterol compared to untreated group. Significant alterations in cardiac marker enzymes: creatine kinase (CK), gamma glutamyl transferase (GGT) and lactate dehydrogenase (LDH) were also observed in serum and heart homogenates of untreated hyperlipidemic rats which were normalized in rats administered the teas. These results are synonymous with decreased risk of atherosclerosis and protective potential on cardiac function by green and black tea. Conclusion: We conclude in this study that regular intake of black and green tea might be useful in treatment of obesity and prevention of cardiovascular complications arising from hyperlipidemia.